A Review of Auraptene as an Anticancer Agent - Tayarani-Najaran, Zahra; Tayarani-Najaran, Nilufar; Eghbali, Samira (Frontiers in Pharmacology, 2021)
Auraptene is a bioactive monoterpene coumarin isolated from Citrus aurantium and Aegle marmelos that belong to the Rutaceae family. Auraptene can modulate intracellular signaling pathways that control cell growth, inflammation and apoptosis and can exert pharmacological properties such as anti-bacterial, anti-fungal, antileishmania and anti-oxidant activity. Auraptene had inhibitory and chemo-preventive effects on the proliferation, tumorigenesis and growth of several cancer cell lines through increase in the activity of glutathione S-transferase, formation of DNA adducts and reduction of the number of aberrant crypt foci. Auraptene exhibits anticancer effects via targeting diﬀerent cell signaling pathways such as cytokines, genes modulating cellular proliferation, growth factors, transcription factors and apoptosis. The present review is a detailed survey of scientific researches on the cytotoxicity and anticancer activity of Auraptene on cancer cells and tumor bearing animals.